Anti-HMG-CoA reductase and antioxidant activities of Sacha inchi (Plukenetia volubilis L.) nutshell extract - Prasongsub, Wattanapong; Pimsan, Nattaporn; Buranapattarachote, Chantanatda; Punturee, Khanittha (Journal of Associated Medical Sciences, 2021)
Background: Hypercholesterolemia is one of the major risks of cardiovascular diseases (CVDs). Hypercholesterolemia and oxidative stress are involved in the pathogenesis of atherosclerosis. Thailand has high percentage of unawareness of hypercholesterolemia, with low percentage of treatment and control. HMG-CoA reductase is a rate limiting step enzyme in cholesterol biosynthesis. Synthetic drugs such as statin are normally used to lower cholesterol level, however it causes adverse effects on the liver and muscle. Thus, HMG-CoA reductase inhibitors of plant origin are needed. Plukenetia volubilis Linneo, commonly known as Sacha inchi or inca peanut is a potential oilseed crop. The seeds of this plant are rich in omega-3 fatty acid. Some studies have shown that consuming Sacha inchi could reduce blood cholesterol. However, the exact mechanism of their lipid lowering activity is still unknown. Objectives: This study aimed to investigate the anti-HMG-CoA reductase, anti-cholesterol esterase and antioxidant activities of different parts of Sacha inchi extracts. Materials and methods: Hot water extracts of 3 different parts of Sacha inchi (nutshell, baby nut and leaf) and Sacha inchi nut oil were evaluated the anti-HMG-CoA reductase and antioxidant activities. HMG-CoA reductase inhibitory activity was determined spectrophotometrically by NADPH oxidation, using HMG-CoA as a substrate. HMG-CoA reductase inhibitory mechanism was also analyzed by using Lineweaver-Burk plot. Antioxidant activity was determined by ABTS and DPPH radical scavenging assay. Total phenolic content was also measured by Folin-Ciocalteu reagent. Moreover, cholesterol esterase inhibition assay was also performed. Results: Sacha inchi nutshell extract revealed the highest anti-HMG-CoA reductase activities at about 99% at concentration of 250 µg/mL, with uncompetitive inhibition in Lineweaver-Burk plot analysis. It also showed the highest cholesterol esterase inhibitory activity around 38% at concentration of 125 µg/mL. Moreover, Sacha inchi nutshell extract also showed the highest antioxidant activity by both ABTS and DPPH assay. Antioxidant activity was correlated to total phenolic content. Conclusion: The experimental data suggested that Sacha inchi nutshell extract is a source of antioxidant compound and may lower cholesterol level by inhibiting HMG-CoA reductase and cholesterol esterase enzymes. Investigation in an in vivo model could further confirm the potential use of Sacha inchi nutshell extract as a supplement for treatment of hypercholesterolemia.